The dynamic impact of oil revenues on public spending and economic growth in Algeria during the period 2000-2019 using the ARDL method - arab, soumia; benbouziane, mohamed (Journal of Research in Finance and Accounting, 2026)
This research paper aims to study the nature of the relationship between oil revenues and both of public spending and economic growth in Algeria. To achieve this, we used the economic measurement methods represented in the ARDL method, the Bounds Test and the ECM error correction model. The results concluded that there is a co-integration relationship between the variables in the long run, and that any short-term change in oil revenues will inevitably affect public spending and the crude internal product of Algeria and push them towards equilibrium in the long term.